2008
DOI: 10.1504/ijmc.2008.017516
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the capacity of the Location-Based Advertising channel

Abstract: Delivering 'relevant' advertisements to consumers carrying mobile devices is regarded by many as one of the most promising mobile business opportunities. The relevance of a mobile ad depends on at least two factors:(1) the proximity of the mobile consumer to the product or service being advertised, and (2) the match between the product or service and the interest of the mobile consumer. The interest of the mobile consumer can be either explicit (expressed by the mobile consumer) or implicit (inferred from user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
(7 reference statements)
1
16
0
Order By: Relevance
“…As we have discussed above, location congruent messages will be more likely to be perceived as relevant for consumers than location incongruent messages, but only if consumers have an actual interest in the advertised product. In line with previous theorizing (Gidofalvi et al, 2008), we therefore expected that location-congruent advertising would be Effects of location-based advertising 12 especially likely to be in line with consumers' goals, and hence more likely to result in increased purchase behavior, decreased perceptions of intrusiveness and more positive ad attitudes, under conditions of high goal relevance. Therefore, our second set of hypotheses was:…”
Section: Hypothesis 1csupporting
confidence: 62%
See 3 more Smart Citations
“…As we have discussed above, location congruent messages will be more likely to be perceived as relevant for consumers than location incongruent messages, but only if consumers have an actual interest in the advertised product. In line with previous theorizing (Gidofalvi et al, 2008), we therefore expected that location-congruent advertising would be Effects of location-based advertising 12 especially likely to be in line with consumers' goals, and hence more likely to result in increased purchase behavior, decreased perceptions of intrusiveness and more positive ad attitudes, under conditions of high goal relevance. Therefore, our second set of hypotheses was:…”
Section: Hypothesis 1csupporting
confidence: 62%
“…The results underline the pivotal role of goal relevance, as this factor not only moderated the effect of Effects of location-based advertising 29 location congruence on behavior, but also had strong main effects on behavior and perceptions of the ad. Gallego et al 2013 Consumer acceptance Survey Gidofalvi et al 2008 Capacity of the LBA channel Simulation study Hühn et al 2012 Consumer impact Experimental study Junglas et al 2008 Consumer acceptance Survey Lee and Hill 2013 Consumer acceptance Survey Lee et al 2012 Consumer impact Interviews with consumers Lin et al 2013 Consumer acceptance Survey Okazaki 2011…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Banerjee and Dholakia (2008) examined the effectiveness of mobile advertising through an experiment that manipulated the location and what the recipients were doing. Gidofalvi, Larsen, and Pedersen (2008) empirically estimated the capacity of the mobile advertising channel based on simulated mobile consumer population from real-world sources and simulated mobile ads offering both the proximity and interest requirements. Xu, Oh, and Teo (2009) empirically examined the effects of multimedia advertisement versus text-based advertisements on consumer perceptions and behaviors in a simulated LBA environment, which showed that multimedia LBA messages led to more favorable attitude, increased the intention to use the LBA application, and had significant impact on purchase intention.…”
Section: Lbamentioning
confidence: 99%